LANGUAGE ART EXHIBITION AS AN INVISIBLE CURRICULUM IN ARABIC LANGUAGE ACQUISITION AT PMDG PUTRI 1ST CAMPUS - Subakir, Fairuz; Rochma, Siti Nikmatul; Khalifah, Nur Fera; Rahmawati, Nuraeni (STKIP Pesisir Selatan, 2025)
This study investigates the Language Art Exhibition as an invisible curriculum in Arabic language acquisition at PMDG Putri Campus 1. Using a qualitative case study approach, the study explores how artistic performances such as drama, poetry recitation (qirā'ah al-syi'r), singing (ghinā'), and news reading (qirā'ah al-akhbār) function as implicit pedagogical mechanisms supporting communicative competence. Data were collected through participant observation, semi-structured interviews, and documentation analysis involving santriyah, Language Advisory Council (LAC) administrators, Arabic supervisors, and pesantren leaders. The findings reveal that the Language Art Exhibition creates a performative language environment encouraging spontaneous Arabic usage, emotional engagement, vocabulary retention, pronunciation accuracy, and speaking confidence. The study further demonstrates that repetitive artistic performances, institutional language culture, peer interaction, and bilingual discipline collectively construct a sustainable language ecosystem facilitating Arabic acquisition through habituation and immersion. The novelty lies in conceptualizing performative invisible curriculum as a framework explaining how artistic activities function pedagogically in pesantren.